Traditional knowledge and uses of gymnosperms in the northeast of Oaxaca, Mexico - Bernal-Ramírez, Luis Alberto; Bravo-Avilez, David; Fonseca-Juárez, Rosa María; Yáñez-Espinosa, Laura; Gernandt, David S.; Rendón-Aguilar, Beatriz (Instituto de Ecología, A.C., 2019)
Background and Aims: Approximately 156 gymnosperm species divided into six families occur naturally in Mexico. Oaxaca has a high richness of gymnosperms, with 45 species, and its inhabitants have an ancient knowledge about the traditional use of this group. The present study contributes to the documentation of traditional knowledge of the gymnosperms in Oaxaca, to evaluate the importance of plant families as useful resources, to understand the relationships between ethnic groups and richness of useful species, as well as to compare our records of gymnosperms with those at state and national levels.Methods: This study was carried out in 84 municipalities within three Priority Terrestrial Regions in the northeast of Oaxaca. The ethnobotanical data were collected through participant observation, ethnobotanical fieldtrips, content-free interviews of the local guides, and botanical specimens were collected. All data were analyzed qualitatively to integrate ethnofloristic and traditional knowledge, as well as ecological aspects of species studied.Key results: We recorded 30 species belonging to the families Cupressaceae, Pinaceae, Podocarpaceae and Zamiaceae. The largest number of useful species (16) registered belongs to Pinaceae. Among the Zapotecs, uses were found for 16 different species, the Mixes use ten and the Mazatec nine. All taxa registered with any use have a common name, 71% in the local language and 97% in Spanish. The most common uses were timber, construction, ornamental and fuel. The montane cloud forest is the vegetation type with the largest number of useful gymnosperms, with 15 species. Forty-five percent of the registered taxa are endemic to Mexico, six species of Pinaceae and eight of Zamiaceae are considered endemic to Oaxaca.Conclusions: This research contributes to increase records of useful gymnosperms in the state of Oaxaca. It is necessary to reconsider and understand the local value of species within the ethnic worldview in order to preserve traditional uses and promote sustainable management programs.